Pengaruh Metode Demonstrasi Terhadap Prestasi Belajar Mata Pelajaran Pemeliharaan/servisSistem Pengapian Konvensional Siswa Kelas XI Semester Genap SMK Tamansiswa Yogyakarta TahunAjaran 2013/2014 - Bahtiar Wilantara; Slamet Priyanto (Jurnal Taman Vokasi, 2014)
This study aims to determine the method of demonstration effect is better than the lecture method of learning achievement maintenance / servicing of conventional ignition systems of SMK Tamansiswa Yogyakarta.This research was conducted at SMK Tamansiswa Yogyakarta in May and June 2014. This type of research is quasi-experimental. The population in this study are 61 students of class XI. The sampling technique using saturation sampling technique. Class XI was chosen from class A and class XI B controls selected as the experimental class. Data collection techniques learning achievement maintenance / servicing of conventional ignition system use a pretest and posttest. Test the validity of the instrument using the judgment experts. Before the items were used for the study, it has been previously tested in class XI C in April 2014. The reliability problem is obtained using the formula K - 20, the results of R11 = 0.933, p = 0.000, so the matter declared reliable. Data analysis techniques were calculated using t-test, prior to the trial to test the prerequisite analysis includes tests of normality and homogeneity tests.Descriptive research results show that the trend of learning achievement maintenance / servicing of conventional ignition systems of class XI student of SMK Tamansiswa Yogyakarta semester academic year 2013/2014 is taught using lecture method included in the medium category and the method of demonstration in the very high category. In the t-test obtained t = 20.200 and p = 0.000, for p < 0.005 means that there are significant differences of learning achievement maintenance / servicing of conventional ignition systems of class XI student of SMK Tamansiswa Yogyakarta semester 2013/2014 academic year. They are taught using the lecture method and demonstration method. Judging from the average hasi turns teaching methods using the method demonstration of 24.345 and 13.897 of the lecture method, this means the method of demonstration effect is better than the lecture method of learning achievement maintenance / servicing of conventional ignition systems of class XI semester Tamansiswa SMK Yogyakarta Academic Year 2013 / 2014 .